SHADOW EDUCATION AND STUDENTS' ACADEMIC ACHIEVEMENT - Kshetree, Arun Kumar; Bhusa, Tilak (Oikos Nomos: Jurnal Kajian Ekonomi dan Bisnis, 2024)
Shadow education is also called private tutoring but it covers many other ways of getting support in studies. It has been very common in Nepal and everywhere in the world since formal education started. This paper is a part of the study with 'Faculty Research Grant' from the University Grants Commission, Nepal. We have studied the different forms of shadow education used by students of high school level asking the teachers teaching in high schools and the students studying bachelor level in different universities in Nepal about their school level experiences regarding shadow education activities and the impact of shadow education in their scores. It was a survey study based on the information gathered from different faculty students studying at the bachelor level. For the research tool we used a questionnaire for the students and a set of interview guidelines for FGD and interviewing the teachers teaching in high schools of three major cities of Nepal; Butwal, Pokhara and Kathmandu. After the analysis of the information gathered, we found that there were different forms of shadowing in education that have been in practice in Nepal and the trend of shadowing has also been changing with the development of ICTs and online applications. We also found that there were majority of the students practising shadow education and it was also revealed that most of the students' achievement in education was promoted by different forms of shadowing. So shadowing in education is a good practice as the teachers viewed that the students involved in shadowing were good in the classes. The paper proves that shadowing needs to be systematized and any unethical practices in shadow education need to be controlled by the concerned authority.